Current practices in influenza management and barriers to influenza vaccination in Nepal - Chokhani, Ramesh (International Journal of Research in Medical Sciences, 2025)
Influenza is a viral infection affecting the respiratory tract, resulting in substantial morbidity and mortality. This review article explores the current practices in influenza management and the barriers to vaccination in Nepal. Influenza-associated respiratory deaths account for approximately 2% of all respiratory deaths globally, with higher mortality rates in low to middle income countries (LMICs) like Nepal. Vaccination remains the most effective preventive measure, yet Nepal lacks a formal seasonal influenza vaccination policy, with vaccines available only in the private sector. Current practices emphasize early diagnosis and antiviral treatment within 48 hours of symptom onset, though delayed diagnosis and poor adherence to treatment guidelines are common in Nepal. The article also discusses the vulnerability of specific populations, including children, pregnant women, individuals with chronic medical conditions, the elderly, and healthcare workers. It underscores the need for improved vaccination coverage and policy changes to reduce influenza-related morbidity and mortality in Nepal. Despite the availability of vaccines, certain barriers limit access to vaccination especially in LMICs like Nepal despite established cost effectiveness of influenza vaccination. Targeted vaccination campaigns and public health education are essential to increase awareness and acceptance.